Genetic variation in taste sensitivity - Prescott, John (Marcel Dekker, 2011)
Featuring results presented at the Sensitivity to PROP (6-n-propylthiouracil) symposium held as a satellite to the European Chemosensory Research Organisation conference in Erlangen, Germany, this volume's field-shaping selections review all sides of PROP sensitivity measurement-from its descriptive worth with regard to sensory experiences, individual taste perceptions, and food choices to its predictive power in the nutrition and public health arenas. Written by recognized names from industry and academia, Genetic Variation in Taste Sensitivity is ideal for taste, olfaction, and flavor chemists and scientists; sensory evaluation chemists and scientists; and nutritionists.